The Legal Protection Regarding Consumer Losses in Banking Transactions Caused by Phishing - Rani Apriani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study is a normative legal study with a conceptual and legislative approach. The results of the study confirm that legal protection that includes the bank's obligation to maintain data security and provide preventive education is very necessary, along with legal resolution of problems if losses occur due to phishing. Strengthening regulations and supervision from the government, the Financial Services Authority (OJK), and banking is very important to minimize the risk of phishing and protect customers effectively. In this case, the bank's legal accountability is key to providing legal certainty and protecting the rights of the injured party, with the condition that the bank can only be held accountable if it is proven negligent in managing data and system supervision. Banks can actually be held accountable either civilly or criminally according to the type and level of the bank's error. This study recommends strengthening stricter regulations, improving data security systems by banks, and providing more comprehensive preventive education to customers regarding potential phishing risks, to ensure optimal protection and minimize potential losses.